Plan de negocio para la creación de una empresa prestadora de servicios de pintura electrostática en la ciudad de Tunja (2021)
This research work seeks to create a company that provides electrostatic painting services in the city of Tunja, specialized in designing, producing and distributing metal parts, painted with electrostatic powder paint, enameling, lacquering and varnishing of metal products, hot-dip galvanizing of metals, engraving of metal products, powder coating of metals, in order to meet the needs and preferences of companies or organizations that wish to furnish and offer unique designs, appropriate colors and highlights for their environment or workspace. The coating of this electrostatic paint is more durable than the conventional ones and more resistant to the different uses to which the different pieces are exposed, it has a hardness and resistance to correction, easy application and great resistance to environmental changes. In the financial evaluation, the Internal Rate of Return (IRR) is 78.53%, which shows that the project is viable.